A new theoretical framework of the law of intergovernmental organizations and its applicability to the European Union - Budai, Péter (Pécs journal of international and European law, 2020)
In some cases, the existing theories about the European Union do not explain coherently some phe- nomena related to European integration, such as the expansion of powers. That issue is so specific that a complex approach is needed. The aim of this study is to show an appropriate theoretical approach which consists of two elements. The first is an element of international political theory, namely the English School, while the second is an element of international jurisprudence, Guy Fiti Sinclair’s approach. Recent literature specifically focused on the special relationship between the foundations of international society and intergovernmental organizations. In my opinion, such an approach would fit to Sinclair’s theory who examined the expansion of powers of intergovernmental organization.